AN ANALYSIS OF BETRAYAL IN PEARL S. BUCK’ THE GOOD EARTH: Betrayal - Muhammad Ainul Yaqin; Cholisotud Diniyah (Fakultas Sastra Universitas Gresik, 2021)
This study discusses the novel pearl s. Bucks the good earth. This study tells about a betrayal, a poor farmer named Wang Lung who married a slave who was willing to sacrifice and accompany wang lung to become a farmer until finally at the peak of success where wang lung became a rich man and began to betray O-Lan by having an affair with Lotus is a beautiful woman who awaits the tea shop. The research will focus on the betrayal and infidelity experienced by O-Lan in the novel. Wang Lung's character in this novel is very influential in the storyline, O-Lan who has been holding back his patience for a long time finally rebelled. and many things that happen in the novel that are closely related to the two, Therefore this research will focus on the betrayal that occurred. The purpose of this study is to discuss the betrayal with infidelity committed by the character Wang-Lung on his wife O-Lan based on observations of novel stories, in order to obtain accurate and more complete data. This research will also be supported by several theories from experts so that the data obtained becomes more focused and the researcher also reads more than once so that all the data obtained becomes more complete. The results of this study indicate the factors that cause betrayal and infidelity. This study can conclude that Wang lung's character has a big influence on the storyline. Loyalty selfishness can have an effect on domestic relationships.